Preparation of Monomeric 2,2-Dymethil-1,3-PropyleneDimethylmalonate; Potential Example of Conformational Isomerism and An Example of the Use of Molecular Models in Research Studies - B. Spencer Meeks; E. Ong Tjong Kiem (Institute for Research and Community Services (LPPM) ITB, 1962)
Dengan penggunaan model2 molekul dapat dilihat kemungkinan adanja suatu isomeri jang stabil dalam senjawa lingkar berinti delapan jalah monomer 2,2